Lindahl's Solution and the Core of an Economy with Public Goods - Foley, Duncan K. (Econometrica, 1970)
In an economy with an arbitrary number of consumers and an arbitrary number of commodities, some public and some private, I propose a generalization of Lindahl's equilibrium solution, and prove an existence theorem for it. A particular generalization of the of an exchange equilibrium to an economy with public goods is proposed, and it is shown that a Lindahl equilibrium allocation is also a core allocation.